Contagious : why things catch on - Berger, Jonah, ....- (New York : Simon & Schuster, 2016)
New York Times bestseller and named Best Marketing Book of 2014 by the American Marketing Association What makes things popular? Why do people talk about certain products and ideas more than others? Why are some stories and rumors more infectious? And what makes online content go viral? If you said advertising, think again. People don't listen to advertisements, they listen to their peers. But why do people talk about certain products and ideas more than others? Why are some stories and rumors more infectious? And what makes online content go viral? Wharton marketing professor Jonah Berger has spent the last decade answering these questions. He's studied whyNew York Times articles make the paper's own Most E-mailed List, why products get word of mouth, and how social influence shapes everything from the cars we buy to the clothes we wear to the names we give our children. In this book, Berger reveals the secret science behind word-of-mouth and social transmission. Discover how six basic principles drive all sorts of things to become contagious, from consumer products and policy initiatives to workplace rumors and YouTube videos. Contagious combines groundbreaking research with powerful stories. Learn how a luxury steakhouse found popularity through the lowly cheese-steak, why anti-drug commercials might have actually increased drug use, and why more than 200 million consumers shared a video about one of the seemingly most boring products there is: a blender. If you've wondered why certain stories get shared, e-mails get forwarded, or videos go viral,Contagious explains why, and shows how to leverage these concepts to craft contagious content. This book provides a set of specific, actionable techniques for helping information spread—for designing messages, advertisements, and information that people will share. Whether you're a manager at a big company, a small business owner trying to boost awareness, a politician running for office, or a health
Keywords: Consumer behaviour; Marketing